The social aspect of water resources management in the Lake Chad Basin: A new construct for water resources management - Nodjidoumde Mbaigoto; Kamal A. Alsharif; Shawn Landry; Tara F. Deubel (PLoS ONE, 2025)
Effective water resource management in developing countries requires a nuanced understanding of the social factors that influence public engagement. This study investigates the relationship between socioeconomic and demographic variables and pro-environmental behaviors (PEBs) in the context of Integrated Water Resources Management (IWRM) in N’Djamena, Chad. A household survey of 582 participants was conducted using purposive sampling, and data were analyzed through chi-square tests, logistic regression, and univariate analysis. The findings reveal that while wealth status does not significantly influence PEBs, education level and gender are strong predictors. Individuals with at least a high school education were 2.5 times more likely to participate in water management meetings than those with less education. Men were also significantly more likely to attend such meetings than women. These results underscore the importance of incorporating educational initiatives and gender-sensitive strategies into water governance frameworks. The study recommends early environmental education and the involvement of community and religious leaders to foster inclusive and sustainable water management practices in the Lake Chad Basin.